What drives subscribing to premium in freemium services? A consumer value-based view of differences between upgrading to and staying with premium - Matti Mäntymäki; A.K.M. Najmul Islam; Izak Benbasat (Wiley, 2022)
Fostering the conversion of free users to premium subscribers and retaining those premium users are critical objectives for freemium service providers. Building on consumer value theory, we empirically examine the differences between basic and premium users in terms of the emotional, functional, social, epistemic, and economic values driving basic users' decisions to upgrade to premium subscriptions and premium users' decisions to retain their paid subscriptions. We employ enjoyment, intrusiveness of advertising in the free subscription, ubiquity, social connectivity, the discovery of new content, and the price value of the premium subscription as drivers of intentions and test our model using data from a leading digital content service that employs the freemium model. Our results show that enjoyment and price value of the premium subscription predict the intention to upgrade to premium, whereas the intention to retain the premium subscription is driven by ubiquity and the discovery of new content. Interestingly, social connectivity has no effect on the intention to upgrade but does have a small negative effect on the intention to retain the premium subscription. Contrary to our expectations, intrusiveness of advertising in the free subscription had a negative effect on the price value of the premium subscription. Collectively, our results imply that the intention to retain the premium subscription is influenced by attribute-level value perceptions such as ubiquity, the discovery of new content, and social connectivity whereas the intention to upgrade is driven by benefits, ie, enjoyment and price value of the premium subscription.